The Cognitive Value of the First Review on the Comedy ”Uncle Balthazar” by Hakob Paronyan - MAKARYAN, ALBERT (Bulletin of Yerevan University B: Philology, 2021)
The article is dedicated to the comprehensive study of the first review written on one of the masterpieces by Hakob Paronyan“Uncle Baghdasar”. It is noticeable that the author of the review (“Criticism on the Comedy “Uncle Baghdasar””) written under the pen-name of “Esther” is the philologist nephew of Paronyan Maksut Santalchyan disguised under the cover of a ferventwoman protectionist of feminism. From the scientific perspective the interesting thing is that this very review was published in the periodical “Khikar” that was edited by Paronyan himself, under his shrewd glance, and, moreover, due to his own wish and honest demand of not giving way to praise but to pay attention only at the “drawbacks” of the play.     And, thus, the aim of the given publication is to thoroughly study this most likely beneficial review, to penetrate into its layers, to reveal, as far as possible, the similarities and differences of the author’s literary credo, world perception and taste with that of Paronyan’s by the same time emphasizing the literary stable apprehensions and vital unique perceptions of the dramatist.
Keywords: Hakob Paronyan; the comedy “Uncle Baghdasar”; periodical “Khikar”; drama; review; reviewer “Esther”; Maksut Santalchyan; feminism; the system of characters; structure; solution